Tom Clancy's endwar : the hunted - Michaels, David, 1955-; Clancy, Tom, 1947-2013.; Copyright Paperback Collection (Library of Congress) (New York : Berkley Books, 2011)
After Saudi Arabia and Iran destroy each other, Russia is determined to rise to global power, forcing America to send an elite strike force to the heart of Moscow to capture an eccentric warrior who holds the key to Russia's next major invasion plan.
"Based on Ubisoft's bestselling game, Tom Clancy's Endwar"--p. [4] of cover.
Keywords: United States. -- Army. -- Special Forces -- Fiction; World War III -- Fiction; Intelligence service -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction; War stories; Adventure fiction